Weak migratory connectivity, loop migration and multiple non‐breeding site use in British breeding Whinchats Saxicola rubetra. (12th April 2020) - Burgess, Malcolm D.; Finch, Tom; Border, Jennifer A.; Castello, Joan; Conway, Greg; Ketcher, Martin; Lawrence, Mark; Orsman, Christopher J.; Mateos, Judit; Proud, Amanada; Westerberg, Stephen; Wiffen, Tina; et al.
Abstract : Determining the links between breeding populations and the pressures, threats and conditions they experience presents a challenge for the conservation of migratory birds which can use multiple sites separated by hundreds to thousands of kilometres. Furthermore, migratory connectivity – the connections made by migrating individuals between networks of breeding and non‐breeding sites – has important implications for population dynamics. The Whinchat Saxicola rubetra is declining across its range, and tracking data from a single African non‐breeding site implies high migratory spread. We used geolocators to describe the migration routes and non‐breeding areas of 20 Whinchats from three British breeding populations. As expected, migratory spread was high, with birds from the three populations overlapping across a wide area of West Africa. On average, in non‐breeding areas, British breeding Whinchats were located 652 km apart from one another, with some likely to share non‐breeding areas with individuals from breeding populations as far east as Russia. Four males made a direct non‐breeding season movement to a second, more westerly, non‐breeding location in January. Autumn migration was through Iberia and around the western edge of the Sahara Desert, whereas spring migration was more direct, indicating an anticlockwise loop migration. Weak migratory connectivity implies that Whinchat populations are somewhat buffered against local changes in non‐breeding conditions. If non‐breeding season processes have played a role in the species' decline, then large‐scale drivers are likely to be the cause, although processes operating on migration, or interactions between breeding and non‐breeding processes, cannot be ruled out.